Study of delta formation factors at Central Greece - ΚΑΡΥΜΠΑΛΗΣ Ε.; ΤΕΓΟΥ Μ.; ΤΣΑΛΚΙΤΖΗ Ο. (Bulletin of the Geological Society of Greece, 2001)
The aim of this study is to determine the correlation between morphological features of the drainage basins of seven Greek rivers (Pinios, Sperchios, Evinos, Acheloos, Arachthos, Louros and Kalamas) and features of their deltas. The Greek mainland is an area with suitable conditions for delta development (high relief, high precipitation, high sediment load, shallow, tectonically inactive, gulfs). Large Greek deltas include wetlands of great environmental importance as well as important areas of great socioeconomic significance. The above rivers have been considered in the present investigation because they all have formed extensive deltas. Furthermore their catchment areas are located entirely within Greece so it was easy to collect elements of great importance about the morphology, the geology and the climate conditions of the studied areas. The morphometric parameters of the drainage basins (drainage basin area, perimeter, total channel length within the basin, contour length within the basin)) were measured using topographic maps at a scale of 1:200.000. The morphological features of the deltaic formations (area of the delta, length of the channel within the deltaic plain) were measured from topographic maps at a scale of 1:50.000. Furthermore morphometric parameters such as drainage density, drainage frequency, slope of the valley and circularity were estimated. In order to determine the influence of the basin lithology upon the evolution of the deltas, the rocks were grouped in five types according to their hydrogeological behavior. A positive correlation between morphometric features of the drainage basins such as the basin area and the length of the main channel of the river and the area of the delta was confirmed while deviation such as the case of Pinios and Louros were determined. The same positive correlation was observed for the slope of the valley and the area of the delta. Elongated basins with rough relief tend to form extensive deltaic formations. Thus is confirmed the importance of the fluvial sediment supply for the evolution and progradation of the Greek deltas. Human activities are another important factor for the future of the deltas. The construction of dams in the upper reaches of the basins caused dramatic reduction in the sediment flux. Human interference includes also the draining of marshy areas, cultivation, fisheries, the artificial diversion and confinement of the main river channel. Another long term natural hazard that will affect the deltaic environment is the projected 34cm sea level rise by the year 2100. It is estimated that the total area of the studied delta that will be inundated by the sea until that year is about 112,7km2.